2020
DOI: 10.31234/osf.io/uarwz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological problems associated with coping strategies: a web-based study in Peruvian population during the COVID-19 pandemic

Abstract: BACKGROUND: The Coronavirus disease has quickly spread to all corners across Latin-American countries. Its exponential capacity has overwhelmed even the most resilient health systems (1). The already significant impact of the Coronavirus (COVID-19) on the global scale is worsened by psychological responses that may aggravate the health crisis. OBJECTIVE: This study is aimed at collecting demographic information, prevalence of psychological morbidities and associated coping styles during the COVID-19 pandemic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…, the quantitative analysis is shown, we found that global averages varied for the subscales of anxiety/insomnia and social dysfunction, whose means are high and are between (M= 1.01; DE = 0.885) and (M= 1.21; DE = 0.942) for items(1,5,8,9,10,11,15,16,17,18,20,21).And the other group, formed by the items(2,3,4,6,7,12,13,14,19,22,23) of the subscales of…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…, the quantitative analysis is shown, we found that global averages varied for the subscales of anxiety/insomnia and social dysfunction, whose means are high and are between (M= 1.01; DE = 0.885) and (M= 1.21; DE = 0.942) for items(1,5,8,9,10,11,15,16,17,18,20,21).And the other group, formed by the items(2,3,4,6,7,12,13,14,19,22,23) of the subscales of…”
mentioning
confidence: 85%
“…-point scale to identify the severity of symptoms between 0 and 3 ("Not at all", "No more than usual", "More than usual" and "Much more than usual"). This version contains 4 subscales: somatic symptoms, anxiety, insomnia, social dysfunction, and severe depression (1).…”
Section: Population and Samplementioning
confidence: 99%
“…Bu ölçek ile grup başa çıkma stratejisi belirlenmektedir: "kendine güvenli yaklaşım (8,10,14,16,20,23,26. maddeler), çaresiz yaklaşım (3,7,11,19,22,25,27,28. maddeler), boyun eğici yaklaşım (5,13,15,17,21,24.…”
Section: Veri Toplama Araçlarıunclassified
“…Araştırmacılar, aktif tepkilerin (kabul ve sosyal destek) psikolojik sorunları olan kişiler tarafından nadiren; pasif stratejilerin ise (inkâr, kendine zarar verme, kendini suçlama, bağlantısızlık ve duygusal boş vermişlik) yaygın olarak kullanıldığını bildirilmektedir. [25] Literatürdeki bu sonuçlar, çalışmamız okuryazar olmayanların diğerlerine göre Sosyal destek arama alt boyut puanlarının anlamlı derecede düşük ve yalnız yaşayan katılımcıların, 6 ve daha fazla kişi ile yaşayanlara göre sosyal destek arama puanlarının anlamlı derecede daha yüksek olduğu sonuçlarını destekler niteliktedir. Buna göre, okuryazar olmayan bireyler ve/veya tek/birkaç kişi ile yaşayanların pandemi sürecinde daha olumsuz baş etme mekanizmalarını kullandıkları söylenebilir.…”
Section: Sosyal Destek Aramaunclassified